Fabrication and characterization of novel hyperbranched polyimides with excellent organosolubility, thermal and mechanical properties. Issue 9 (18th October 2014) - Chen, Wenqiu; Li, Quantao; Zhang, Quanyuan; Xu, Zushun; Wang, Xianbao; Yi, Changfeng
ABSTRACT A series of amine‐terminated and anhydride‐terminated hyperbranched polyimides (HBPIs) were successfully prepared with various commercial dianhydrides and a novel BB′2‐type aromatic triamine, 2, 4, 6‐tris[4‐(4‐aminophenoxy)phenyl]pyridine, with a symmetrical triaryl‐substituted pyridine segment and prolonged flexible linkages. The chemical structure of the triamine monomer and the hyperbranched structure of the resulting polymers were verified by Fourier transform infrared spectroscopy and 1H‐NMR spectroscopy. The resulting HBPIs, which mainly held an amorphous morphology, exhibited improved organosolubilities in several strong polar aprotic solvents, good heat resistance with glass‐transition temperature values in the range 218.6–311.0°C, and excellent thermal stabilities in both N2 and air [the temperature at 5% weight loss (T5%) in N2 was higher than 529.8°C and the T5% in air was higher than 465.1°C]. The obtained HBPI films also showed outstanding mechanical properties with tensile strength, tensile modulus, and elongation at break values of 86.4–101.3 MPa, 1.73–2.04 GPa, and 5.07–10.67%, respectively; considerable optical transparency; low water absorption; and neutral interface wettability. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41544.